Experimental Determination of Relative Marginal Utilities - Mera, Koichi (Quarterly Journal of Economics, 1969)
I. Introduction, 464. — II. Test of alternative principles in taxation, 467. — III. The social value of government expenditure, 474. — Appendix, 476.